Descobrindo as rimas em poemas: estudo sobre os efeitos das rimas na consciência fonológica e suas relações com os demais níveis de consciência linguística durante o processo de alfabetização - Wolff, Clarice Lehnen (2015)
This study investigates the rhyme in children poems as a linguistic event that triggers the increase of linguistic awareness and boosts the understanding of language processing strategies, focusing on its role in learning how to read and write in early literacy period. This research was conducted in two stages. In the first one, in nine poetry and phonological awareness transcription workshops developed in a first grade group, behaviors of rhyme awareness were identified, categorized, and integrated to other levels of the phonological level itself and to other linguistic levels (morphological, syntactic, semantic, textual, pragmatic ones). In the second stage, after analyzing these behaviors, the most frequent ones and/or the most relevant to the study were selected in order to elaborate a phonological awareness assessment tool integrated with linguistic awareness. It is a qualitative tool that helps to outline a profile to order to identify behaviors that need more stimulation in the linguistic awareness process for pedagogical actions in classrooms. Methodology for pedagogical parameters to work with poetry in early literacy period was made from the literary reviews, the identified behaviors of linguistic awareness, and the nature of the profile brought for by the assessment tool. Thus, from the reflection on the rhyme possibility to link words in verses, the phonological awareness concept was expanded regarding the relationship between behaviors of this very level of awareness and phonological awareness with other levels of linguistic awareness. The phonological, semantic and syntactic levels were the most demanded into this integrated process in the literacy period, as pointed out by Gombert (1992). The rhymes impelled the attention of children to the sound structure of words, which favored the identification of more possibilities in the segmentation of speech and aspects related to the temporality of the sounds that help in learning. It was also verified the importance of the coming and going movement related to the phonological, syntactic and semantic awareness of the language from words to text by the children.